Electron image contrast analysis of mosaicity in rutile nanocrystals using direct electron detection. Issue 6 (23rd October 2020) - Yoon, Aram; Shao, Yu-Tsun; Howe, Jane; Zuo, Jian-Min
Abstract : High‐resolution electron microscopy image contrast obtained from a rutile nanocrystal using direct electron detection is quantified and interpreted based on a model of mosaic crystals. Abstract : Direct electron detection provides high detective quantum efficiency, significantly improved point spread function and fast read‐out which have revolutionized the field of cryogenic electron microscopy. However, these benefits for high‐resolution electron microscopy (HREM) are much less exploited, especially for in situ study where major impacts on crystallographic structural studies could be made. By using direct detection in electron counting mode, rutile nanocrystals have been imaged at high temperature inside an environmental transmission electron microscope. The improvements in image contrast are quantified by comparison with a charge‐coupled device (CCD) camera and by image matching with simulations using an automated approach based on template matching. Together, these approaches enable a direct measurement of 3D shape and mosaicity (∼1°) of a vacuum‐reduced TiO2 nanocrystal about 50 nm in size. Thus, this work demonstrates the possibility of quantitative HREM image analysis based on direct electron detection.